2002
DOI: 10.1046/j.1445-6664.2002.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathy of buckwheat: Assessment of allelopathic potential of extract of aerial parts of buckwheat and identification of fagomine and other related alkaloids as allelochemicals

Abstract: The allelopathic potential of buckwheat (Fagopyrum esculentum) was investigated. Field study showed that living buckwheat reduced weed biomass compared with plots without buckwheat. Laboratory study revealed that root exudates suppressed root and shoot growth of weeds and reduced weed dry weight. Sequential partitioning of the aqueous ethanolic extract of the aerial parts of buckwheat showed that the chloroform extract caused an 80% reduction in radicle elongation of lettuce seedlings at a concentration of les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 9 publications
2
34
0
1
Order By: Relevance
“…It is also reported that susceptibility of a target plant to phytotoxic extracts Data represent mean value of each parameter; * same letters in each column indicate no significant difference at 5%, after applying LSD test of a donor plant depends on the plant organs used in preparing the extracts (Iqbal et al 2002;Kobayashi 2004). In our study, test plants responded differently to P. harmala aqueous extracts.…”
Section: Discussionmentioning
confidence: 74%
“…It is also reported that susceptibility of a target plant to phytotoxic extracts Data represent mean value of each parameter; * same letters in each column indicate no significant difference at 5%, after applying LSD test of a donor plant depends on the plant organs used in preparing the extracts (Iqbal et al 2002;Kobayashi 2004). In our study, test plants responded differently to P. harmala aqueous extracts.…”
Section: Discussionmentioning
confidence: 74%
“…Flavonoids, such as quercitrin, were identified by Siqueira et al (2011) from the ethanol extract of leaves of Blepharocalyx salicifolius (Myrtaceae). Quercitrin has phytotoxic activity (Iqbal et al, 2002) and may be related to the inhibitory results observed here. Still, the work carried out by Romero et al (2012) and Suyenaga et al (2007) identified phenolic compounds, anthraquinones, saponins and tannins in leaf extracts of B. salicifolius.…”
Section: Discussionmentioning
confidence: 84%
“…Based on the hypothesis that phytotoxic compounds found in buckwheat tissues may be released into the soil during plant decomposition, several studies focus on assessing the inhibitive effect of buckwheat extracts. Aqueous ethanolic extracts of aerial parts reduced radicle elongation of lettuce by 25% (Iqbal et al, 2002). Leaves extracts had the highest inhibitive effect on the root elongation of several weeds (Hayashi, 1998;Ohsawa and Nakatani, 2005) followed by shoot and inflorescence extracts (Golisz et al, 2007).…”
Section: Allelopathic Compounds Released During Decompositionmentioning
confidence: 99%